Dynamics and Factors of ESG Adoption in the Czech Republic - Balogh, Ivan; Tyll, Ladislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2026)
Businesses in the Czech Republic are increasingly exposed to regulatory, market, and stakeholder pressures to improve corporate environmental performance, strengthen ESG transparency, and communicate sustainability-related information credibly. This dissertation examines the organizational and contextual mechanisms through which firms respond to these pressures, with a particular focus on absorptive capability, environmental strategy, corporate environmental management performance, ESG disclosure intensity, firm-level factors, and the perceived importance of environmental claims in purchasing decisions. The dissertation consists of three empirical papers. The first paper employs covariance-based structural equation modelling (CB-SEM) to analyse internal ESG adoption based on questionnaires collected from senior managers of large Czech companies. The second paper complements this perspective by examining firm-level determinants of ESG disclosure intensity using censored regression models. The third paper applies generalized ordinal logistic regression to investigate how consumers’ individual predispositions relate to the perceived importance of environmental claims for product and service purchases. Taken together, the three papers provide a multi-level perspective on ESG adoption in the Czech context. The findings indicate that absorptive capability is positively associated with environmental strategy and indirectly associated with corporate environmental management performance through environmental strategy. In addition, firm-level characteristics, particularly company size measured by revenue and number of employees, as well as industry ESG sensitivity and profitability, are associated with higher observed ESG disclosure intensity.
The findings further suggest that the perceived importance of environmental claims in purchasing behaviour is associated with anthropogenic climate change beliefs, green self-efficacy, and sustainability related communication from government institutions. Overall, the dissertation suggests that stronger environmental and ESG adoption outcomes are associated not only with compliance-oriented reporting, but also with firms’ ability to internalise sustainability knowledge, align environmental initiatives strategically, and communicate environmental performance in ways perceived as credible by stakeholders. The thesis contributes to the ESG and dynamic capabilities literature by offering an integrated, multi-level perspective on environmental strategy, environmental performance, and firm-level ESG disclosure determinants within a Central European regulatory setting shaped by the Corporate Sustainability Reporting Directive.
Vedoucí práce: Ladislav Tyll
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: management a manažerská ekonomie [obor disert. práce]; disertace; dissertations